Concrétiser les opportunités de l'économie des plateformes par la liberté syndicale et la négociation collective - Felix Hadwiger (Organisation internationale du Travail, 2022)
This study provides empirical evidence from different regions of the world to identify avenues for platform economy workers to access freedom of association and collective bargaining. It shows that collective protests, the establishment of new organizations of workers and platforms, social dialogue and, to a limited extent, collective bargaining are taking place in the platform economy. The experiences from the ground described in this study indicate ways and a demand to create an even more enabling environment for freedom of association and collective bargaining in order to realize the opportunities of the platform economy for workers and employers.
Keywords: 330; future of work; employment; non-standard forms of employment; digital labour; labour relations; collective bargaining; collective agreements; labour law; gig economy; workers rights; freedom of association; information and communication technologies